2001
DOI: 10.1046/j.1365-2591.2001.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Periapical lesion progression and cytokine expression in an LPS hyporesponsive model

Abstract: Responsiveness to LPS may not be significant in the pathogenesis of periapical lesions and in cytokine expression within the lesions, when the lesions are induced by non-specific oral flora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
15
0
3
Order By: Relevance
“…30 Larger lesions may also be slower to heal completely, and therefore appear to have incomplete healing in some studies. 26 Numerous studies have used lesion size to examine the pathogenesis and healing of PR lesions in animal models and have documented their findings in terms of lesion size either histomorphometrically [31][32][33][34] or radiographically. [35][36][37] More studies are needed to determine if the radiographic size of PR lesions in patients is related to the virulence of root canal microorganisms and if the rate of reduction in size correlates with the effectiveness of treatment.…”
Section: Epidemiology and Pathogenesis Of Periradicular Lesionsmentioning
confidence: 99%
“…30 Larger lesions may also be slower to heal completely, and therefore appear to have incomplete healing in some studies. 26 Numerous studies have used lesion size to examine the pathogenesis and healing of PR lesions in animal models and have documented their findings in terms of lesion size either histomorphometrically [31][32][33][34] or radiographically. [35][36][37] More studies are needed to determine if the radiographic size of PR lesions in patients is related to the virulence of root canal microorganisms and if the rate of reduction in size correlates with the effectiveness of treatment.…”
Section: Epidemiology and Pathogenesis Of Periradicular Lesionsmentioning
confidence: 99%
“…, Kawashima & Stashenko , Kent et al . , Fouad & Acosta ). In addition, LPS can induce the expression of cytokines and chemokines and elicit the innate immune response in DPSCs (Chang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Lipopolysaccharide (LPS) is a major component of the gram-negative bacterial membrane that persists in dentine and resists its elimination and is responsible for pulp infection (Vianna et al 2007). Lipopolysaccharide can induce the expression of pro-inflammatory cytokines and chemokines, such as TNF-a, IL-6 and IL-8, and elicit a variety of immune responses in the odontoblasts, fibroblasts and monocytes of dental pulp tissue (Nagaoka et al 1996, Kawashima & Stashenko 1999, Kent et al 1999, Fouad & Acosta 2001. In addition, LPS can induce the expression of cytokines and chemokines and elicit the innate immune response in DPSCs (Chang et al 2005).…”
mentioning
confidence: 99%
“…). In addition, IL‐6 levels were measured at 2, 4, 6 and 8 weeks, and increased expression was observed at 8 weeks (Fouad & Acosta ). Another study suggested that macrophages and osteoblasts are involved in the development of periapical lesions and that they promote bone resorption by producing mediators such as IL‐6 (Lin et al .…”
Section: Resultsmentioning
confidence: 99%